A Security Adaptation Reference Monitor for Wireless Sensor Network. (23rd August 2012) - El-Maliki El-Maliki, Tewfiq Tewfiq; Seigneur Seigneur, Jean-Marc Jean-Marc
Abstract : Security in Wireless Sensor Network has become a hot research topic due to their wide deployment and the increasing new runtime attacks they are facing. We observe that traditional security protocols address conventional security problems and cannot deal with dynamic attacks such as sinkhole dynamic behavior. Moreover, they use resources, and limit the efficient use of sensor resources and inevitably the overall network efficiency is not guaranteed. Therefore, the requirements of new security mechanisms must be addressed in a flexible manner. Indeed, there is a lack of generic security adaptation protocols to deal with extremely dynamic security conditions and performances in a context of Wireless Sensor Network where reliability is a critical criterion for many applications. This paper proposes our Security Adaptation Reference Monitor for Wireless Sensor already validated in proximity-based wireless network. It is based on an autonomic computing security looped system, which fine-tunes security means based on the monitoring of the context. Extensive simulations using agent-based approach have been conducted to verify the performance of our system in the case of sensor network in the presence of sinkhole attacks. The results clearly show that we are efficient in terms of survivability, overall network utilization, and power consumption.